Witwatersrand-Type Paleoplacer Gold in the Huronian Supergroup of Ontario, Canada - Mossman, D.; Harron, G. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1984)
Summary There are encouraging signs of the potential of the Huronian Supergroup to host Witwatersrand-type paleoplacer gold. A total of thirty-one Au or Au-U occurrences are recognized as being stratiform. Of these, two occur in the Cobalt Group, four in the Quirke Lake Group, nineteen inthe Hough Lake Group and six in the ElliotLake Group. The greatest number of occurrences are located in the Matinenda and Mississagi Formations of the Elliot Lakeand Hough Lake Groups. Gold in basal Huronian rocks is related to basement geology and to a local source. Exciting recent finds in the upper Huronian Lorrain Formation in the northern half of the Cobalt Embayment represent extensively re-worked fluvial deposits in braided streams distant from the provenance of the gold. Geological conditions closely resemble those of the Witwatersrand. Sedimentological studies hold the key to locating the more attractive concentrations of gold.